2019
DOI: 10.3390/diseases7030050
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence and Correlation of Carotid Artery Calcifications and Dental Pulp Stones in a Saudi Arabian Population

Abstract: Background: This study sought to determine the prevalence of carotid artery calcifications (CACs) and pulp stones detected on panoramic radiographs (PRs) and ascertain their correlation. Methods: A total of 2013 digital PRs were retrospectively retrieved and thoroughly examined to determine the prevalence of CACs and pulp stones, their correlation with patient age and gender, and the relationship between the presence of pulps stones and radiographically detectable CACs. Results: The prevalence of CACs on PRs w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
19
1
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 34 publications
3
19
1
4
Order By: Relevance
“…What is known is that there are similarities in the calcification processes (Carson, 1998;Kohri et al, 2012;Foster et al, 2018), with an exacerbation of the inflammatory process (Gopal et al, 2016). Another highlight is that the incidence of pulp stones is higher in patients with diabetes and kidney disease (Nakajima et al, 2013), including urolithiasis (Movahhedian et al, 2018;Gabardo et al, 2019), and coronary artery disease (Alsweed et al, 2019). In addition, there are evidence in the literature that female individuals are more affected (Ravanshad et al, 2015;Jannati et al, 2019), but other authors have not confirmed this information (Hsieh et al, 2018;Babu et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…What is known is that there are similarities in the calcification processes (Carson, 1998;Kohri et al, 2012;Foster et al, 2018), with an exacerbation of the inflammatory process (Gopal et al, 2016). Another highlight is that the incidence of pulp stones is higher in patients with diabetes and kidney disease (Nakajima et al, 2013), including urolithiasis (Movahhedian et al, 2018;Gabardo et al, 2019), and coronary artery disease (Alsweed et al, 2019). In addition, there are evidence in the literature that female individuals are more affected (Ravanshad et al, 2015;Jannati et al, 2019), but other authors have not confirmed this information (Hsieh et al, 2018;Babu et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…To summarize, high prevalence of pulp stones has been reported globally (Jannati et al, 2019) and may be associated with other systemic conditions (Nakajima et al, 2013;Alsweed et al, 2019;Gabardo et al, 2019). Additionally, sialometric and sialochemical evaluations are relevant to research in this field, to understand the etiology of diseases and discover potential salivary biomarkers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mineral deposits can be formed in ectopic areas or dystrophic lesions under various conditions in the body [1], this mineral deposition can make changes with the appearance of a lesion or plaque and be observed radiographically [1].…”
Section: Introductionmentioning
confidence: 99%
“…Few authors have reported a significant association between renal calculi and PS [ 9 ]. Moreover, researchers believe that PS detection can be a diagnostic marker of systemic disease [ 10 , 11 ]. Cardiovascular disease (CVD) is a major concern of morbidity and mortality in the modern era.…”
Section: Introductionmentioning
confidence: 99%